Development of a Web-Based Graduation Document Completeness Information System - Annisa Gatri; Cahya Vikasari; Nur Muniroh (Politeknik Piksi Ganesha Indonesia, 2026)
The manual graduation administration process causes data errors, incomplete documents, and legal risks such as diploma revocation. This study aims to develop a web-based graduation document information system to automate final project document verification and improve graduation administration accuracy and efficiency. The study used the waterfall method, including requirements analysis, database and interface design, implementation with PHP and MySQL, and black-box testing. The system features student data management, an 8-document checklist (including file upload), automation of eligibility status, a statistical dashboard, and three report levels. Testing on 47 scenarios achieved a 100% success rate. The web-based system effectively improves graduation data accuracy, eliminates human error, and supports digital transformation of academic services. Further development requires adding student roles and automatic notifications.